Efﬁcacy and Safety of Metformin in Gestational Diabetes Mellitus - Huma Muzaffar; Shama Chaudhry; Nigar Sadaf; Rubina Hussain (ziauddin University, 2024)
Background: Gestational Diabetes Mellitus (GDM) is a sequence of serious unfavorable maternal and perinatal outcomes specially if uncontrolled. Although insulin is a standard therapy, Metformin can be used as an alternative medication to insulin. This study aimed to establish the efﬁcacy, safety, and other metabolic effects of metformin in GDM due to limited studies in the local population. Methods: This quasi experimental trial was conducted on pregnant female at 24 weeks of gestation and above, presenting to Ziauddin Hospital. A total of 361 patients who were diagnosed with GDM were enrolled. Patients were divided into three groups: diet control, metformin, and metformin with insulin. The Chi Square and ANOVA were used to compare the maternal and neonatal outcomes. Further post hoc analysis of signiﬁcant parameters was done using Tukey HSD test. Results: Weight gain in pregnancy and gestational age at delivery gives signiﬁcant mean differences across three study groups (p=<0.01). In diet control group, weight was signiﬁcantly gained as compare to metformin group. Similarly, the gestational age in diet control group was signiﬁcantly higher as compare to metformin and metformin with insulin group (p=<0.01). The higher gestational age was found in patients treated with metformin as compared to metformin with insulin group (37.25±1.41). Conclusion: Metformin alone as well as in combination with insulin, is a safe, effective treatment option and more acceptable to women with GDM. Metformin has shown to cause less weight gain during pregnancy with minimal risk of maternal and neonatal hypoglycemia. Keywords: Gestational Diabetes Mellitus; Metformin; Insulin